Caught in the geopolitical tensions between China and the United States: Impacts on Chinese students pursuing American higher education - Wang, Xin (Journal of International Students, 2024)
Drawing on the survey data from 259 students enrolled at American universities, the study explores how recent tensions between China and the U.S. and issues of public safety would affect Chinese students’ perceptions and aspirations for American education. The findings of the research identify significant correlations between the effects of U.S. policies regarding Chinese students, concerns about U.S. public safety, and the impact of U.S. foreign policy toward China on Chinese students at American universities. Students’ responses reveal how the pursuit of an American college education remains deeply intertwined with broader societal dynamics and geopolitical realities, which challenge the aspirations of Chinese students for education abroad in an increasingly deglobalizing world.